TINGKAT KELAYAKAN PENERIMAAN KARYAWAN SEBUAH PERUSAHAAN “XYZ” DENGAN METODE FUZZY LOGIC - Siti Masripah (LPPM Universitas Bina Sarana Informatika, 2010)
Employees are the most valuable asset for a company, therefore the human resource in every company will surely find and select prospective employees who will work at the company. The problem that often occurs is difficult to determine the company's prospective employees because many employees are applying for and a lot of existing candidat. Therefore needed a tool of the company in determining the best candidat. With Fuzzy Logic method and calculations will be performed perangkingan feasibility value of each prospective employee with some parameters as acauan in the assessment. Thus helping the company in determining the desired candidates.Keywords: Fuzzy Logic, Employee, Worthiness